Halomonas smyrnensis sp nov., a moderately halophilic, exopolysaccharide-producing bacterium - KAZAN, DİLEK (MICROBIOLOGY SOC, 2013)
Four Gram-negative, moderately halophilic, exopolysaccharide-producing strains, designated AAD6(T), AAD4, AAD17 and AAD21, were isolated from Camalti Saltern Area, a wildlife reserve in Sasali, Izmir province located in the Aegean Region of Turkey. The isolates grew at an optimum NaCl concentration of 10% (w/v). The major cellular fatty acids were C-16:0, C-18:1 omega 7c, C-16:1 omega 7c and C-12:0 3OH, respectively and the predominant lipoquinone was ubiquinone Q-9. The G+C content of the genomic DNA of strains AAD6(T), AAD4, AAD17 and AAD21 was 63.0, 63.3, 62.8 and 62.6 mol%, respectively. Comparative 16S rRNA gene sequence studies showed that the isolates belonged to the genus Halomonas. The DNA-DNA hybridization mean values between the representative strain AAD6(T) and the closely related species Halomonas saline DSM 5928(T), Halomonas halophila DSM 4770(T), Halomonas maura DSM 13445(T), Halomonas organivorans DSM 16226(T), Halomonas elongate DSM 2581(T), Halomonas koreensis JCM 12237(T) and Halomonas nitroreducens LMG 24185, were 40.8, 39.6, 24.2, 23.3, 12.6, 14.5 and 12.2%, respectively. Based on these data the strains represent a novel species of the genus Halomonas for which the name Halomonas smyrnensis sp. nov. is proposed. The type strain is AAD6(T) (=DSM 21644(T)=JCM 15723(T)).
Keywords: AD-HOC-COMMITTEE; DELEYA-SALINA; SOLAR SALTERN; FAMILY; GENUS; CHROMOHALOBACTER; DECARBOXYLASE; STRAINS; LAKE